DEVELOPMENT OF AN INTEGRATED COMMUNICATION SYSTEM FOR 5G-BASED AUTONOMOUS VEHICLES - Alkautsar Rahman; Felipe Souza; Raul Gomez; Rahmi Setiawati; Ardi Azhar Nampira (Journal of Moeslim Research Technik, 2025)
The rapid advancement of autonomous vehicle technology necessitates robust communication systems to ensure safety, efficiency, and connectivity. The emergence of 5G technology presents opportunities to enhance communication capabilities for autonomous vehicles, enabling real-time data exchange and improved decision-making. This research aims to develop an integrated communication system for autonomous vehicles utilizing 5G technology. The study focuses on evaluating the performance, reliability, and latency of the proposed system in various driving scenarios. An experimental approach was employed, involving the design and implementation of a 5G-based communication framework for autonomous vehicles. Various tests were conducted in controlled environments to assess communication latency, data throughput, and system reliability. Different vehicular scenarios, including urban and highway driving, were simulated to evaluate performance under diverse conditions. The findings indicated that the integrated 5G communication system achieved a latency of less than 10 milliseconds, significantly enhancing real-time data transmission. Data throughput exceeded 1 Gbps, demonstrating the capability to support high-bandwidth applications. The system exhibited robust performance across various driving scenarios, with minimal data loss and high reliability. The research demonstrates the potential of 5G technology in transforming communication systems